Membangun Jurnalisme Wisata Sejarah Berkelanjutan di Desa Wisata Tamansari, Banyumas - Khristianto, Khristianto; Nurhayati, Sulasih; Saepuddin, Encep; Montezza, Ana Mae (Jurnal SOLMA, 2025)
Background: Background: Tourism villages generally need help with marketing due to the lack of community involvement in these efforts. As a result, the content and news on their websites often need to be updated. This activity aims to enhance the writing skills of tourism journalism cadres in Tamansari, Banyumas. Method: In order to achieve this goal, a training program includes three stages: presentations, field observations for material/data collection, and writing practice. Results: Based on the results and evaluations conducted, it can be concluded that the training program was quite successful. This is evident from three main indicators: 1) the training participants showed a high enthusiasm for attending the training (100%), and they are also committed to promoting (100%) their village. During the implementation, the number of participants remained intact (100%) and engaged in every activity stage with total commitment. A post-training survey also supports this positive trend. The majority (75%) felt the training went well, and they also experienced the benefits of the activity. With this positive perception, they also expressed readiness (100%) to create/write news and to promote tourism (100%). They demonstrated this by submitting news writing assignments in class or individual tasks at home. Their writings required minimal editing (3-5%) and were ready for publication. Conclusion: The mentoring provided awareness of the importance of promoting and utilizing the younger generation to contribute by channeling their abilities to create journalistic works that highlight tourism information in their villages.